Value of routine blood count surveillance in detecting relapse in acute lymphoblastic leukemia - AlHarbi, Sarah; Taha, Areej; Ashi, Ahmed; Elimam, Naglla; Althubaiti, Sami (Frontiers in Pediatrics, 2025)
BackgroundChildren with acute lymphoblastic leukemia (ALL) have excellent outcomes, with >85% survival without relapse following contemporary therapies. Clinical and complete blood count (CBC) assessments are commonly used surveillance methods to detect relapses. We aimed to evaluate the efficacy of routine blood testing for detecting relapse using a systematic method of assessing normal and abnormal results.MethodsThis a retrospective, single center study included children aged 1–14 years diagnosed with ALL who completed therapy and were in complete remission. Demographic data, leukemia subtypes, risk stratification, treatment responses, and outcomes were also reviewed. CBC tests were evaluated, and abnormal results were categorized. The relapse groups were classified as asymptomatic and symptomatic relapses. The clinical outcomes of relapse and complications were analyzed. The sensitivity, specificity, positive predictive value, and negative predictive value of surveillance laboratory tests for predicting relapse after the end of treatment were evaluated.ResultsIn total, 187 patients underwent 2074 CBC tests. Ten patients underwent full surveillance, whereas the remaining patients underwent partial surveillance. The median number of surveillance blood draws per patient was 12. Relapse was observed in nine patients. Only three patients had asymptomatic relapses. Neutropenia, leukopenia, pancytopenia, thrombocytopenia, and anemia were observed in 98, 89, 10, 6, and 3 patients respectively. The sensitivity and specificity of neutropenia, leukopenia, thrombocytopenia, anemia, and pancytopenia were 11.11% and 47.9%, 0% and 50%, 33.3% and 98.31%, 0% and 99.4%, and 33.3% and 96.07%, respectively. No differences were observed between patients who had asymptomatic relapses and those whose clinical outcomes or consequences had symptomatic relapses.ConclusionRelapse after completion of therapy in ALL is rare. Regular blood count surveillance does not predict clinical outcomes or relapse. Prospective studies are required to assess appropriate risk-based surveillance and its effects on patient outcomes and quality of life.